Acute cholecystitis: review of 500 observations - Parma, Dante; Armand Ugon, César; Ant´unez, Carlos; Otazu, Heber; Farcic, Antonio; Delgado, Bolívar (Cirugía del Uruguay, 1980)
Review of 500 case histories of acute cholecystitis and treatment and compariso'n of' rcsul'ting statistic